Islamic Law, Women's Rights, and State Law : The Cases of Female Genital Cutting and Child Marriage - Wodon, Quentin (Taylor and Francis, 2015)
Issues related to Islamic law, women’s rights, and state law have long been and remain deeply contested. This is most evident in debates around family law reform in majority Muslim countries. As one recent example, in Mali, a secular state according to its Constitution, the National Assembly adopted in August 2009 a new family code proposed by the government. The new code included provisions to set the minimum age for marriage at 18; change inheritance rules for women including the ability for them to remain in their dwelling upon the death of their husband; change rules for adoption and the recognition of children born out of wedlock; define marriage as a secular and public act that should be ratified by the state; and protect the integrity of the human body (which relates among others to the issue of female genital cutting or FGC). In some countries arguments inspired by Islamic law have been used in order to suggest that prohibiting FGC and child marriage could be “un-Islamic,” and faith leaders have substantial influence on whether the practices persist or not. Mali is a case in point.